Analysis of Cultural Intelligence (CQ) and the Huma Betang Philosophy Among Local Communities in Palangka Raya - Dharma Alkautsar Mahadika; Ilham Nur Alfian; Duta Nurdibyanandaru; Euis Nurhidayati; Rury Eryna Putri (Green Publisher Indonesia, 2026)
Indonesia's multicultural landscape provides a rich context for examining the relationship between local cultural philosophy and Cultural Intelligence (CQ). This study investigates how the Huma Betang Philosophy of the Dayak community in Palangka Raya City, Central Kalimantan, shapes and reinforces Cultural Intelligence among local residents amid rapid social change. Huma Betang, the traditional longhouse of the Dayak people, embodies core values of togetherness, mutual cooperation (gotong royong), tolerance, and deliberative consensus, which collectively serve as a cultural foundation for navigating diversity. Using a qualitative ethnographic approach, data were collected through unstructured in-depth interviews with four purposively selected participants, comprising community leaders, cultural researchers, a former mayor, and an academic anthropologist, all with deep knowledge of Dayak culture and the Huma Betang philosophy. The findings reveal that the Huma Betang Philosophy significantly strengthens all four dimensions of Cultural Intelligence: Cognitive CQ through a profound understanding of Dayak cultural history; Metacognitive CQ through critical reflection on cultural change driven by globalization and digitalization; Motivational CQ through a deep sense of cultural pride and responsibility toward heritage preservation; and Behavioral CQ through adaptive and inclusive actions in multicultural interactions. However, the implementation of this philosophy also faces considerable challenges, including external cultural influence via social media, intergenerational value differences, and the commercialization of cultural heritage. The study concludes that with appropriate educational programs, active youth engagement, and strategic use of digital media, the Huma Betang Philosophy can serve as a sustainable cultural resource for maintaining Dayak identity.